Possible Scotlands : Walter Scott and the story of tomorrow - McCracken-Flesher, Caroline (Oxford University Press, 2005)
Is Walter Scott to blame for the limitations of modern Scotland? The author argues that Scott used his position as an author to negotiate an identity for his homeland. The variety of Scott's tales suggest not a Scotland receding into the past, but one energetically alive in the past and future of its telling.